2018
DOI: 10.1097/txd.0000000000000755
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression Adherence in Stable Kidney Transplant Patients Converted From Immediate- to Prolonged-Release Tacrolimus in Clinical Practice: A Norwegian Study

Abstract: BackgroundThis study investigated medication adherence in kidney transplant patients (KTPs) converted from immediate-release tacrolimus (IR-T) to prolonged-release tacrolimus (PR-T)-based immunosuppression in routine practice.MethodsNoninterventional, observational, multicenter study in Norway. Included adult KTPs with stable graft function, converted from IR-T (baseline) to PR-T (1 mg:1 mg) in routine practice. Data were collected at baseline, and months 1, 3, 6, and 12 postconversion. Primary endpoint: adher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
(38 reference statements)
1
16
0
1
Order By: Relevance
“…Finally, this is a study performed during the first post‐transplant year and may not reflect the patient′s overall IS medication intake behaviour during later years. A recently published Norwegian study using BAASIS © during later post‐transplant years showed a higher nonadherence prevalence . During the 1‐year follow‐up, the present study did not demonstrate a worsening in renal function or AR in NoAd patients.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this is a study performed during the first post‐transplant year and may not reflect the patient′s overall IS medication intake behaviour during later years. A recently published Norwegian study using BAASIS © during later post‐transplant years showed a higher nonadherence prevalence . During the 1‐year follow‐up, the present study did not demonstrate a worsening in renal function or AR in NoAd patients.…”
Section: Discussionmentioning
confidence: 99%
“…As many of the developed tools do not evaluate the timing perspectives, an important aspect of immunosuppressive adherence is missing. BAASIS ® has established predictive validities the recent years and is today the most frequently used adherence questionnaire in transplant recipients (194,(202)(203)(204)(205)(206). BAASIS ® follow the recent ABC taxonomy of medication adherence (160), and assess adherence using items of dose taking, timing, drug holidays, drug reduction and discontinuation.…”
Section: Patient Self-reportmentioning
confidence: 99%
“…Our study was in agreement with a similar multi-centre study involving over a thousand renal transplant patients whereby it was found that renal functions remained stable upon conversion . Even though a study by Abedini et al have reported a stable renal function following conversion (15), it could well be attributed to the reduced tacrolimus exposure following conversion. Although there may be some protective effect on renal function with the use of Advagraf®, due to the lower single peak exposure observed in this current study, a prospective multicentre study should be conducted in the future to demonstrate if this benefit is of clinical significance.…”
Section: Discussionmentioning
confidence: 96%